Cardioprotective effect of Pycnogenol in ischemic-reperfusion injury (IRI) in rats - Xiao, P.; Zhang, K.; Tao, Z.; Liu, N.; Ge, B. (Cellular and Molecular Biology, 2017)
Oxidative stress plays a critical task in the biochemical and pathological alteration linked with myocardial ischemic-reperfusion injury (IRI). This warrants identifying agents with a potential for preventing such damage in an effective way. A novel plant based product, Pycnogenol, obtained from the French maritime pine (Pinus pinaster ssp. atlantica) bark extract was known for its tremendous antioxidant potential (both in vivo, in vitro). It was able to attenuate the symptoms of immune dysfunction through restoring a cellular antioxidant status in low micronutrient-induced immune deficient mice. Consequently, the present study was deals with the determination of protective effect of Pycnogenol in ischemic–reperfusion injury (IRI) in rats via Non-recirculating Langendorff's technique. The effect of Pycnogenol on the level of various key biomarkers in the rat heart homogenate was determined, such as, myocardial thiobarbituric acid reactive substances (TBARS, a marker of lipid peroxidation), lactic dehydrogenase (LDH) (a marker of tissue injury) and effect on endogenous antioxidants, e.g., superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and glutathione peroxidase (GPx). The activity of these biomarkers appreciably improved in Pycnogenol-treated group than IRI group (P < 0.05). The effect of Pycnogenol was further confirmed via histopathological examination of cardiac tissues, which suggests that, it considerably improved the injury related to tissue damage through suppression of edema and infiltration of neutrophil compared to IRI group. It also showed modulation of the expression of apoptotic factors, e.g. Bcl-2, bax and caspase-9 as confirmed by western blot analysis.